A Theoretical Focus on Cultural Taxation: Who Pays for It in Higher Education - Cleveland, Dr. Roger; Sailes, Dr. JaDora; Gilliam, Dr. Erin; Watts, Jillian (Advances in Social Sciences Research Journal, 2018)
The representation of faculty of color at universities and colleges in the United States has increased. Yet, white professors still account for 84% of full-time faculty. Researchers suggest that along with institutionalized racism the mantra of publish or perish promotes racial disparities in academia. The scholarly demand of publishing is encumbered by all tenure track faculty. However, non-white faculty faces additional challenges as they pursue promotion and tenure. “Cultural taxation” is one of the most major occupational threats for faculty of color. This theoretical paper examines how “cultural taxation” may serve as an obstacle to success for faculty of color in the academy due to implicit and explicit discriminatory practices.